MECOM/PRDM3 and PRDM16 Serve as Prognostic-Related Biomarkers and Are Correlated With Immune Cell Infiltration in Lung Adenocarcinoma - Li, Meng; Ren, Hui; Zhang, Yanpeng; Liu, Na; Fan, Meng; Wang, Ke; Yang, Tian; Chen, Mingwei; Shi, Puyu (Frontiers in Oncology, 2022)
Background: The MDS1 and EVI1 complex locus (MECOM, also called PRDM3) and PR domain containing 16 (PRDM16) are two highly related zinc finger transcription factors associated with many malignancies. However, the mechanisms of MECOM and PRDM16 in prognosis and tumor immune infiltration in lung adenocarcinoma (LUAD) remain uncertain. Methods: The Cancer Genome Atlas (TCGA), Oncomine, UALCAN, GEPIA and TIMER database were conducted to determine the relationship between the expression of MECOM and PRDM16, clinicopathological features, immune infiltration, and prognosis in LUAD. Co-expressed genes of the two genes were investigated by CBioPortal and the potential mechanism of MECOM and PRDM16 related genes was elucidated by GO and KEGG analysis. STRING database was utilized to further construct the protein-protein interaction network of the co-expressed genes, and the hub genes were identified by Cytoscape. Finally, qRT-PCR was performed to identify the mRNA levels of the target genes in LUAD. Results: mRNA levels of MECOM and PRDM16 were down-regulated in LUAD (P<0.05), and the low expression of the two genes was associated with the age, gender, smoking duration, tissue subtype, poor stage, nodal metastasis status, TP53 mutation, and prognosis in LUAD (P<0.05). MECOM and PRDM16 were also found correlated with the expression of a variety of immune cell subsets and their markers. KEGG analysis showed that both of them were mainly enriched in the cell cycle, cellular senescence, DNA replication, p53 signaling pathway. Importantly, the mRNA levels of the two genes were also identified decreased in the clinical samples of LUAD by qRT-PCR. Conclusion: MECOM and PRDM16 may serve as potential prognostic biomarkers which govern immune cell recruitment to LUAD.